Elaboración de una Guía Turística de la Parroquia de Mindo, perteneciente al Cantón San Miguel de los Bancos Provincia de Pichincha - Cevallos Villalba, Gladys Patricia (2015)
This investigation is the base to elaborate a Tourist Guidebook of the Mindo Parish, which is located in the canton of San Miguel de los Bancos. This project has three chapters: The first chapter is an assessment of the general characteristics of the Mindo Parish. This is important because it permit us to know the current status of Mindo and through this assessment which got the accurate data of the tourist activities taking place in the parish of Mindo. The second chapter is an inventory of natural and cultural attractions. This information was gotten through gathering and the identification the tourism potential in Mindo. The third chapter is the development of the tourist guidebook with the information obtained throughout the investigation process, in order to promote tourism in the parish of Mindo. Mindo has a lot of natural attractions because flora and fauna of the Protected Forest Mindo Nabillo’s, where there are many species of birds (hummingbirds, cock it) plants (orchids) and insects (butterflies). Also extreme sports are practiced. This makes Mindo like a natural paradise for all national and internationals tourists.